Moral Error Theory Without Epistemic Error Theory: Scepticism About Second-Personal Reasons. (2nd December 2019) - Rowland, Richard
Abstract: Proponents of the epistemic companions in guilt argument argue that we should reject the moral error theory because it entails that there are no epistemic reasons. In this paper, I investigate whether a plausible version of the moral error theory can be constructed that does not entail an error theory about epistemic reasons. I argue that there are no irreducibly normative second-personal reasons even if there are irreducibly normative reasons. And epistemic reasons are not second-personal reasons. In this case, a plausible version of the moral error theory can be constructed that does not entail an error theory about epistemic reasons if facts and claims about morality entail facts and claims about irreducibly normative second-personal reasons. And, as I explain, there is a good case that facts and claims about morality do entail facts and claims about irreducibly normative second-personal reasons.